Magnetic susceptibility from the Blue Lias Formation from five sites in southern Britain, UK - Graham P Weedon; Hugh C Jenkyns; Kevin N Page (PANGAEA, 2018)
Measurements of volume magnetic susceptibility (vol MS) measured in the field at five sections of the Blue Lias Formation in southern Britain, UK. The sites are Pinhay Bay to West Cliff, Lyme Regis (Dorset); St Audries Bay (Somerset); Quantocks Head (Somerset); St Marys Well Bay at Lavernock (Glamorgan); Southam Quarry, near Long Itchington (Warwickshire). Each data set includes: stratigraphic height; astronomically tuned time scale; composite time scale; vol MS (SI units); short eccentricity filter output; lithology of measurement; previously published bed number; ammonite biohorizon, ammonite subzone; ammonite zone. In the case of limestone nodules within light marl measurements are made through the limestone nodules if they constitute 50% or more of the section along the bedding planes. For horizons with widely spaced limestone nodules (< 50% along bedding) light marl is measured instead. Volume MS measurement procedures are described by Weedon, Jenkyns and Page (2018). Astronomical tuning, filtering and the composite time scales are described by Weedon, Page and Jenkyns (2018).
Supplement to: Weedon, Graham P; Page, Kevin N; Jenkyns, Hugh C (2019): Cyclostratigraphy, stratigraphic gaps and the duration of the Hettangian Stage (Jurassic): insights from the Blue Lias Formation of southern Britain. Geological Magazine, 156(9), 1469-1509, https://doi.org/10.1017/S0016756818000808